Evaluation of Zeolite, Nanomagnetite, and Nanomagnetite-Zeolite Composite Materials as Arsenic (V) Adsorbents in Hydroponic Tomato Cultures - Escudey-Castro, A; Escudey-Castro, A; Zuniga-Navarro, G; Pizarro-Arriagada, C; Pizarro-Arriagada, C (Elsevier B.V., 2021)
There is a growing interest in the use of adsorbent nanoparticles to mitigate the toxic effects of pollutants in natural matrices. However, due to their small size, nanoparticles have the potential to transport and disseminate contaminants adsorbed on their surfaces into environmental compartments with greater risk to human, animal, or plant health. This potential consequence of nanoparticle application remains largely unstudied. Here, we studied the application of three adsorbents, including zeolite (Z, micrometric size), nanomagnetite (Mt), and a nanomagnetite-zeolite composite (MtZ) intended to mediate arsenic toxicity in hydroponic tomato cultures. Adsorption studies showed an arsenate adsorption sequence of MtZ (6.2 mg g−1) ≥ Mt (4.7 mg g−1) ≫ Z (0.3 mg g−1). Tomatoes grown under the Mt condition demonstrated the lowest growth rate (4.2 cm), corresponding to a 45% decrease compared to the control (7.6 cm), as well as the highest oxidative stress level (0.024 μmol g−1) as indicated by malondialdehyde (MDA) concentration, almost twice the control (0.014 μg g−1). Tomatoes grown under MtZ conditions showed a 22% decreased growth (5.9 cm) but MDA levels (0.012 μmol g−1) were comparable to the control. Together, these results suggest that Mt at the nanometric size could obstruct channels in the plant and prevent absorption of water and nutrients. Anchoring nanomaterials in larger composites of micrometer size presents a promising alternative that would retain their super-adsorbent properties while avoiding toxicity due to nanometric size. © 2020 Elsevier B.V.
Keywords: Supported nanoparticles; Plant remediation; Iron oxides nanomaterials